Stres w pracy nauczyciela – wybrane uwarunkowania - Szczygieł, Magdalena (Kultura-Społeczeństwo-Edukacja, 2020)
Stress aspects still remain as an existing problem, which requires further interdisciplinary studies. Considering the strong impact of chronic exposure to psychosocial stressors at a workplace in relational and incentives contexts of undertaking professional duties, those aspects gain in importance in teachers’ work. A person stays in a continuouscontact with a student, parent or another teacher, and their motivation seems to be a key aspect for the entire education process. The presented article is an attempt to capturestress indicators in a teachers’ work, as well as ways of dealing with them in a school reality. The article begins by highlighting the most important stress definitions, followed by a brief methodology of self-research. Then the author describes stressors present in teacher’s work, which were identified in empirical studies, and ways of dealing with stress used by tested teachers. The article ends with conclusions and recommendations for further representative studies.